Implications of COVID-19 pandemic for energy-use and energy saving household electrical appliances consumption behaviour in Malaysia - Mustapa S.I.; Rasiah R.; Jaaffar A.H.; Abu Bakar A.; Kaman Z.K. (Elsevier Ltd, 2023)
Energy efficiency; Surveys; Consumption levels; Control orders; COVID-19; Energy efficient; Energy-consumption; Energy-savings; Household electrical appliances; Malaysia; Movement control; Movement control order; Energy utilization